Morphological and structural modification of CaGe2 by annealing with MgCl2/Mg. (1st April 2023) - Sekino, Kaito; Shimura, Yosuke; Tatsuoka, Hirokazu
Abstract: Ge-based nanosheets and GeH phases were synthesized in the vapor phase using CaGe2 crystals as templates. Ge-based nanosheets have been synthesized in the liquid-phase, but not in the vapor-phase. Compared with liquid-phase synthesis, vapor-phase synthesis is more useful for nanostructure control and impurity addition technologies. These technologies will increase the future popularity of nanosheets. And it is important to apply these technologies after clarifying the effects of certain parameters, such as annealing temperature and changes in the mole fractions. As an introduction to the future development of vapor-phase synthesized Ge-based nanosheets, this study proposes the thermal annealing of CaGe2 powders with MgCl2 . Furthermore, the effects of changing the molar fraction containing Mg atoms and the behavior of HCl were investigated from 100 °C–600 °C.